Modulation of Prepulse Inhibition and Startle Reflex by Emotions: A Comparison between Young and Older Adults - Le Duc, Jolyanne; Fournier, Philippe; Hébert, Sylvie (Frontiers in Aging Neuroscience, 2016)
This study examined whether or not the acoustic startle response and sensorimotor gating may be modulated by emotions differentially between young and older adults. Two groups of participants (mean age Young: 24 y.o.; Elderly: 63.6 y.o.) were presented with three types of auditory stimuli (Startle alone, High or Low frequency Prepulse) while viewing pleasant, neutral, or unpleasant images. Electromyographic activity of the eyeblink response was measured. Results show that older adults displayed diminished eyeblink responses whereas younger adults displayed enhanced eyeblink responses when viewing negative images. Sensorimotor gating also differed between young and older adults, with enhanced sensorimotor gating abilities while viewing positive pictures in older adults and diminished abilities while viewing negative pictures among younger adults. These results argue in favor of a differential emotional influence on the sensorimotor abilities of young and older adults, with a positivity bias among the latter.